Digital Literacy and Self-Directed English Learning Behaviors among Generation Z Students in Vocational Animal Health - Gadis Kartika Pratiwi; Esra Rombeallo; Rahayu Asmadini Rosa; Ni Wayan Apsari Shantika Pratistha (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2026)
The rapid integration of digital technology in education makes it essential to examine how digital literacy influences students’ learning behaviors, particularly among Generation Z who are often assumed to be inherently digitally competent. However, previous studies tend to emphasize technical skills and access, while overlooking how these competencies translate into autonomous learning practices. This study addresses this gap by investigating the relationship between digital literacy and self-directed English learning among first-year students of the Animal Health Study Program in a vocational higher education context. Using a descriptive quantitative design, data were collected through a structured questionnaire and analyzed using descriptive statistics to identify patterns across digital skills, exposure, and learning behaviors. The analysis involved categorizing responses into key dimensions and interpreting trends to answer the research questions. The findings reveal a discrepancy between high digital exposure and low engagement in autonomous English learning, highlighting that digital familiarity does not necessarily foster independent learning. This study contributes by emphasizing the need to integrate critical digital literacy and learner autonomy in instructional design. Future research is recommended to employ inferential analysis and mixed methods to further explore this relationship and to develop more effective pedagogical strategies.